Predictors of In-Hospital Mortality in Acute Myocardial Infarction (Medical Forum Monthly, 2024)
Background: Acute myocardial infarction is the leading cause of death. This study was conducted to identify the predictors of in-hospital mortality in acute myocardial infarction.Study Design: Prospective cross sectional studyPlace and Duration of Study: This study was carried out at AK CMH/SKBZ MZD from January1st 2011 to 31st December 2012..Materials and Methods: This prospective cross sectional study was carried out at AK CMH/SKBZ MZD from January1st 2011 to 31st December 2012 of 151 patients having acute first ever acute myocardial infarction (AMI). Of these 151 patients 133 were discharged from the hospital and 18 died. Both categories were analyzed regarding sex; age; time elapsed from onset of the symptoms of myocardial infarction to assistance at the hospital; family history of AMI ;use of streptokinase; risk factors foratherosclerosis and electrocardiographic location of myocardial infarct.Results: Among 151patients, 114 (75.5%) were males and 37 (24.5%) were females. Mean age was56.59 ±14.47.Out of theses 67 (44.3) received streptokinase. Hospital mortality was 12% (18/151) within 14 days. Age and age category has impact and gender has no impact on mortality .Age category (p=0.02), Hypercholesterolemia (p=0.043), Time of onset of chest pain to SK given (p=<0.001), left ventricular failure (p=0.001) asystole (p=0.001) and ventricular septal defect (VSD) (p=0.007) on admission were important prognostic predictors of mortality in AMI. Mortality associated with AMI needs control and prevention of modifiable risk factors. Mean time of onset of chest pain to SK given was 2.62±1.46 hours. In-hospital mortality in SK was 8(11.9%) (p=0.002). Complication of AMI such as asystole 6(75%), VSD 3(50%) and LVF 13(27.7%) has statistically significant predictors of higher in-hospital mortality.General Linear Model (GML),Multivariate statistical analysis revealed that topical presentation of AMI, test between the subject effect association of hypertension with age p=0.036 vs. age category p=0.030) (hypertension p=0.059 vs. mortality p=0.018),hypertension level ( SBP level p=0.0001vs DBP p=0.137) ,cholesterol level with mortality (p=0.006) , AF with mortality (p=0.047), duration of chest pain with mortality (p=0.002) and streptokinase with in-hospital mortality (p=0 .01) and anteroseptal or extensive anterior infarction(p=0.034)had statistical significant association with in-hospital mortality.Conclusion: Age category, Time of onset of chest pain to SK given, left ventricular failure, asystole and ventricular septal defect (VSD) on admission were statistically significant predictors of mortality in AMI. Mortality associated with AMI needs prompt management and its prevention by control of modifiable risk factors.